Análise imunohistoquímica de marcadores de proliferação celular e da p53 em cistos dentígeros, queratocistos e ameloblastomas unicísticos - Lima, Glauber Meira (2003)
The identification of the proliferative activity in cysts and tumors has been pointed as an important aspect in the avaliation of the biologica behavior among different lesions. The proliferating cells nuclear antigen (PCNA) and the Ki-67 are the most used molecular markers in detection of proliferating cells. Mutations in p53 tumor suppressor gene can produce more stable protein, however with loss of function. The greater stability mutation p53 allows its immunohistochemical detection and this technique has been used in avaliation of biological behavior of neoplasic and cystic lesions. The dentigerous cysts (CD), odontogenic keratocyst (QO) and the unicystic ameloblastoma (AU) are benign lesions that have its origin in disturbs in the tooth formation. Despite the clinical and radiografic similarity, these lesions have a distinct biological behavior. Betwen then, QO and AU are the most aggressive lesions and can recur when submitted to conservative treatment. The present work has the objective of studing, through immunohistochemical, the expression of PCNA, Ki-67 and p53 in 15 QOs, 10 CDs and 5 AUs. The average of the percentage of PCNA+ and Ki 67+ cells countained in QOs (46,4 and 13, 7%) was significanting higher than the CD (26,2 and 7,9%). The AUs presented the labeling index for the PCNA (35,9%) statistically similar to that observed in QOs (P=0136), however, compared to Ki-67 (24,4%), the AUs had a bigger labeling index. Although both markers have been used in detection of cell proliferation, a larger average of marked cells for the PCNA it was observed in all the samples. Thirty three percent of the keratocyst cases presented a positivety for the p53. Only one case of dentigerous cysts was positive. It wasn’t any case of unicystic ameloblastoma. Although the detection of the protein p53 for immunohistochemical be considered a mutated variation, the benign clinical behavior of these lesions suggest a larger stability of this protein in it’s repair function.